Preparation of Ti/Sn-SbOx/β-PbO2-Ta2O5 composite anode by pulsed electrodeposition and its electrochemical properties - Guo, Junjie; Jiang, Cheng; Gao, Chao; Chen, Buming; Huang, Hui; He, Yapeng; Guo, Zhongcheng; Guo, Jun; Xu, Ruidong (Solid state ionics, 2024)
In this paper, Ti/Sn-SbOx/β-PbO2-Ta2O5 composite electrodes were prepared by pulsed electrodeposition, the doping amount and the mechanism of Ta2O5 embed into the gap between PbO2 particles was analysized. The effect of Ta2O5 doping on microstructure and cyrstal structure and electrochemical performance of electrodes were was characterized by scanning electron microscopy (SEM), X-ray diffractometry (XRD), X-ray photoelectron spectroscopy (XPS), and Inductively Coupled Plasma (ICP). The surface of the electrode became flatter and denser with appropriate amount of Ta2O5 doping, leading to the improvement of the electrocatalytic activity of the electrode. The effect of Ta2O5 doping on the electrochemical performances of the electrodes were analyzed by linear scanning voltammetry (LSV), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). The service life and failure mechanism of Ti/Sn-SbOx/β-PbO2-Ta2O5 composite electrodes were investigated by accelerated life corrosion test and SEM. Finally, the possibilities possibility application of the Ti/Sn-SbOx/β-PbO2-Ta2O5 composite electrodes in the area of copper electrowinning test was investigated. •Ti/Sn-SbOx/β-PbO2-Ta2O5 composite electrodes were prepared by pulsed electrodeposition.•The electrochemical properties of the composite electrode was improved by Ta2O5 doping.•The cell voltage in copper electrode simulation tests redeced after Ta2O5 doping.